A prototype model for chaos studies - Uçar, A (Pergamon-Elsevier Science Ltd, 2002)
In this paper, a simple model is proposed for chaos studies. The model consists of a state, time delay and a nonlinear element. It can be described as an autonomous continuous-time difference-differential equation with only one variable. The rich behaviour of the system is numerically illustrated. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: time delay; chaotic model; bifurcation diagram; nonlinear feedback systems